Medical education in Obstetrics and Gynecology: preferences of medical students regarding digital teaching - Cirkel, Christoph; Tauber, Nikolas; Krawczyk, Natalia; Scharf, Jann Lennard; Rody, Achim; Banys-Paluchowski, Maggie (Frontiers in Medicine, 2025)
BackgroundThe aim of this survey is to determine students’ preferences of the University Lübeck in Germany regarding various supplementary digital learning opportunities in the field of Gynecology and Obstetrics in order to better address students’ needs and to improve and modernize teaching.MethodsAn online questionnaire was carried out from the Medical Education Team of the Department of Gynecology and Obstetrics at the University Medical Center Schleswig-Holstein, Campus Lübeck among students during the gynecology rotation at the end of summer semester 2023.ResultsA total of 117 students participated in this online questionnaire [32 male (28%) and 84 female (72%) students]. Hybrid lectures (participation either online or in the lecture hall) were preferred by 111 students (96%), whereas only 2 students (1.7%) favored exclusively in-person attendance. Online learning opportunities were rated as highly or very highly valuable by 93 students (80%). Online learning tools were mainly used for exam preparation [108 students (92%)], for targeted deepening of specific topics [82 students (70%)], to catch up on missed lectures [85 students (72%)] and to review or repeat a lecture content [83 students (71%)].ConclusionTraditional teaching methods such as practical exercises and “bed-side teaching”/patient contact are still highly valued by medical students, which students wish to see expanded. Additional online learning opportunities such as on-demand lectures are increasingly important in medical education and are very appreciated by students. Findings indicate that lecturers may consider these needs of the new medical student generation.